The Responsible Research and Innovation (RRI) Maturity Model: Linking Theory and Practice - Stahl, Bernd Carsten; Obach, Michael; Yaghmaei, Emad; Ikonen, Veikko; Chatfield, Kate; Brem, Alexander (Sustainability, 2017)
Responsible research and innovation (RRI) is an approach to research and innovation governance aiming to ensure that research purpose, process and outcomes are acceptable, sustainable and even desirable. In order to achieve this ambitious aim, RRI must be relevant to research and innovation in industry. In this paper, we discuss a way of understanding and representing RRI that resonates with private companies and lends itself to practical implementation and action. We propose the development of an RRI maturity model in the tradition of other well-established maturity models, linked with a corporate research and development (R&D) process. The foundations of this model lie in the discourse surrounding RRI and selected maturity models from other domains as well as the results of extensive empirical investigation. The model was tested in three industry environments and insights from these case studies show the model to be viable and useful in corporate innovation processes. With this approach, we aim to inspire further research and evaluation of the proposed maturity model as a tool for facilitating the integration of RRI in corporate managemen
Keywords: Industry; Innovation process; Maturity model; R&D management; Responsible research and innovation; RRI